Environmental impacts of shallow water mining in the Baltic Sea - Dargahi, Bijan (Frontiers in Marine Science, 2023)
This study investigated the environmental risks of seabed mining for metal resources in the Baltic Sea using a combination of hydrodynamic, particle-tracking, and sediment-transport models. The models were applied for ten years i.e., 2000-2009 under prevailing conditions to simulate seabed mining operations. The focus was on sediment concentration near the seabed and its spread. The mean background concentrations were low with small seasonal bed-level variations throughout the Baltic Sea Basin. Late summer and early autumn periods were the most active. Seabed mining significantly alters the dynamics of sediment suspensions and bed level variations. The concentrations increase unsustainably to high levels, posing a serious threat to the ecological health of the Baltic Sea. The Gotland basins in the Baltic Sea are the most susceptible to mining. The bed level variations will be ten-fold, exposing the highly contaminated sediments at the seabed to the flow. In less than a year, 30-60% of the total particles released in each basin reached the thermocline layers. This study suggests that seabed mining in the Baltic Sea is not sustainable.